Glycaemic profile changes by highly active antiretroviral therapy in human immunodeficiency virus-infected patients. (October 2015) - Duro, M; Rebelo, I; Barreira, S; Sarmento-Castro, R; Medeiros, R; Almeida, C
To study dysglycaemia in human immunodeficiency virus (HIV)-infected patients we conducted a retrospective cohort study of the glucose profile in HIV-infected patients. The fasting blood glucose was analysed taking into consideration conventional risk factors as well as HIV infection and highly active antiretroviral therapy (HAART). One hundred seventy-three cases were selected for this study. Five risk factors had significant effects ( p < 0.05) on glucose levels: age, body mass index (BMI), hepatitis C virus/hepatitis B virus (HCV/HBV) co-infection, viral load (VL), and CD4 + T-lymphocyte count. Fasting blood glucose levels increased with age (0.59 mg/dL/year), decreased with the VL (−4.1 × 10 −6 mg/dL/number of viral RNA copies) and the CD4 + T-lymphocyte count (−0.016 mg/dL/cell count). Furthermore, obese patients and those co-infected with HCV/HBV were more prone to develop dysglycaemia having, on average, 15.4 mg/dL and 13.8 mg/dL higher levels, respectively, of fasting blood glucose. Despite an increase of 1.0% and 8.4% in the glucose levels noticed among HIV patients treated with non-nucleotide inhibitors of reverse transcriptase and protease inhibitors, respectively, HAART did not prove to be a significant predictor of fasting glucose levels as well as lipodystrophy and male gender. Age, BMI, HCV/HBV co-infection and HIV-related (VL and CD4 + T-lymphocyte count) factors seem to be the most influential on fasting blood glucose levels in HIV-infected individuals.